Analysis of Factors Affecting the Decision to Visit Tourists to Religious Tourism (Universitas Negeri Semarang, 2022)
This study aims to identify the pull factors of tourist destinations that must be considered to improve the decision to visit tourists to Religious Tourism in Pati Regency, and to analyze the effect of service quality, distance, facilities, tourist attraction, and travel costs on the decision to visit tourists to Religious Tourism in Pati Regency. The sample of this research is 96 tourists using accidental sampling techniques. The data collection method used is a questionnaire. The analytical method used is descriptive analysis, factor analysis, and regression analysis. The results of the factor analysis test, there are 2 pull factors for tourist destinations that must be considered to increase the decision to visit Religious Tourism in Pati Regency which consists of factors of excellence in tourist destination and the travel overview factor. The results of multiple linear regression analysis show that the quality of services, facilities, and tourist attractions have a significant positive effect on visiting decisions, distance has no significant effect on visiting decisions, while travel costs have a significant negative effect on visiting decisions. Penelitian ini bertujuan untuk mengidentifikasi faktor-faktor penarik destinasi wisata yang yang harus dipertimbangkan untuk meningkatkan keputusan berkunjung wisatawan ke Wisata Religi Kabupaten Pati, dan untuk menganalisis pengaruh kualitas pelayanan, jarak, fasilitas, daya tarik wisata, dan biaya perjalanan terhadap keputusan berkunjung wisatawan ke Wisata Religi Kabupaten Pati. Sampel penelitian ini sebanyak 96 orang wisatawan dengan menggunakan teknik accidental sampling. Metode pengumpulan data yang digunakan adalah kuesioner. Metode analisis yang digunakan adalah analisis deskriptif, analisis faktor, dan analisis regresi.Hasil dari pengujian analisis faktor terdapat 2 faktor penarik destinasi wisata yang harus dipertimbangkan untuk meningkatkan keputusan berkunjung wisatawan ke Wisata Religi Kabupaten Pati yang terdiri dari faktor keunggulan daerah tujuan wisata dan faktor gambaran perjalanan. Hasil dari analisis regresi linear berganda bahwa kualitas pelayanan, fasilitas, dan daya tarik wisata berpengaruh positif signifikan terhadap keputusan berkunjung, jarak tidak berpengaruh signifikan terhadap keputusan berkunjung, sedangkan biaya perjalanan berpengaruh negatif signifikan terhadap keputusan berkunjung.